Investing in hedge funds : a guide to measuring risk and return characteristics - Bali, Turan G.; Atilgan, Yigit; Demirtas, Ozgur; ScienceDirect eBooks (Oxford : Academic, 2013)
Participants in financial markets are not a homogeneous group. Different investors have a unique set of risk and return expectations that have changed significantly over the past few decades. The asset management industry has managed to increase its size exponentially due to its ability to satisfy these expectations. Consequently, there have always existed a set of alternative investments that are designed to service those investors who do not want to settle for the risk and return combinations that traditional investments offer but prefer to experiment with novel asset classes. The composition of this alternative set of investments has also evolved remarkably through time. Several decades ago high-yield bonds, emerging market equities, and real estate were considered to be alternative. Today, such investments would rather be classified as traditional. The current alternative investments are private equity, venture capital, precious metals, commodities, and even art works. One of the most important items on this list is hedge funds.
Chapter 1. Introduction -- chapter 2. Hedge fund strategies -- chapter 3. Hedge fund databases, biases, and indices -- chapter 4. Risk-adjusted performances of hedge fund indices -- chapter 5. Determinants of hedge fund index returns.
Includes bibliographical references.
Online resource; title from pdf information screen (Ebsco, viewed July 23, 2013).
Safari Books Online
Elsevier
Keywords: Hedge funds; Investments; Financing, Personal; Investments; BUSINESS & ECONOMICS -- Investments & Securities -- Futures; Hedge funds; Investments; Electronic books